Ingestion of melamine cleaning sponges-derived microplastic fibers affects the survival and reproduction of Daphnia magna - Huimin Li; Wenwen Song; Songfeng Wang; Yanhua Wang; Yunfeng Ma; Yu Su; Rong Ji (Ecotoxicology and Environmental Safety)
The abrasion of melamine cleaning sponges release microplastic fibers (MPFs) into the environment, yet the potential risks remain unknown. Here, we evaluated the ingestion, elimination, and toxic effects of melamine MPFs on Daphnia magna through acute and chronic exposures. This new type of MPFs displayed different morphology (a combination of linear and branched fibers with a length ranging from 10 to 157 μm) from the widely-studied MPFs released from textiles (longer and thicker linear fibers but no branched fibers). Although the lethality of melamine MPFs to neonates was not observed upon a short-term exposure (24 h), such effect was detected when the animals were exposed for a longer period (21 d) and showed a concentration-dependent manner. The MPFs tended to aggregate in the gut of D. magna, leading to a slow elimination compared to polystyrene microspheres. The MPFs remaining in the gut triggered an elevation in the intracellular reactive oxygen species, which further induced oxidative damage and eventually death. The long-term exposure to MPFs also stimulated D. magna to produce more offspring. Our findings show the chronic toxicity of the sponges-derived MPFs to typical freshwater zooplankton and accentuate the environmental impacts related to the extensive use of the sponges.